Meeting Patient and Professional Needs: Views of Stakeholders on a Training Initiative for Dwsis in Endodonti CS in London. Issue 2 (May 2016) - Al-Haboubi, Mustafa; Newton, Paul; Gallagher, Jennifer E
Background and aims: A pilot scheme was established across London to train NHS primary dental care practitioners to provide endodontic treatment of moderate difficulty. It was co-led by the former London Deanery (Health Education England: North West London) and local NHS commissioners. This research aimed to explore key stakeholders' perceptions about the purpose of the initiative, its advantages, disadvantages and future implications. Methods: Nineteen semi-structured interviews were conducted with stakeholders (commissioners and providers of the educational initiative; commissioners and providers of care, including trainees, principal dentists and specialists) involved in establishing, running and participating in the initiative and wider endodontic service provision in London. Interviews were based on a topic guide informed by the literature, and a workshop involving the London trainees. Interviews were recorded, transcribed and analysed using framework methodology. Results: The project was perceived as supporting four key areas: addressing services, improving quality/outcomes, delivering education and enhancing professional status. There was evidence that dentists were harnessing health policy in facilitating 'reprofessionalisation' of dentistry with the creation of dentists with enhanced skills (DwSIs). Learning outcomes from the pilot were related to the accreditation of the participants, service tariffs, reimbursement for endodontic treatment on the NHS, and the need for continuity within and between services across the dental system. Uncertainty about funding and the changes within the NHS were among the concerns expressed regarding the future of the initiative. Conclusion: The findings of this research suggest that extending the skills of primary care practitioners may contribute to the reprofessionalisation of dentistry, which has much to contribute to patient care and the development of an integrated and accessible dental care system of quality, with improved outcomes for patients. The implications for health policy and further research are discussed.